2023
DOI: 10.3390/ijerph20053825
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Pandemic on Adherence to Chronic Therapies: A Systematic Review

Abstract: The spread of the coronavirus disease 2019 (COVID-19) pandemic caused a sudden and significant disruption in healthcare services, especially for patients suffering from chronic diseases. We aimed at evaluating the impact of the pandemic on adherence to chronic therapies through a systematic review of available studies. PubMed, EMBASE, and Web of Science were searched since inception to June 2022. Inclusion criteria were: (1) observational studies or surveys; (2) studies on patients with chronic diseases; (3) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 81 publications
0
21
0
Order By: Relevance
“… 37 , 38 A systematic review by Olmastroni et al assessed the impact of COVID-19 on medication adherence of many chronic conditions such as inflammatory bowel disease, COPD, osteoporosis, psoriasis and others. 39 Overall, they showed that adherence to the chronic therapies were reduced during COVID-19; some examples included biologics, controller inhalers and denosumab injections. Reasons for decreased adherence were difficulty in reaching physicians, fear of infection and unavailability of medications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 37 , 38 A systematic review by Olmastroni et al assessed the impact of COVID-19 on medication adherence of many chronic conditions such as inflammatory bowel disease, COPD, osteoporosis, psoriasis and others. 39 Overall, they showed that adherence to the chronic therapies were reduced during COVID-19; some examples included biologics, controller inhalers and denosumab injections. Reasons for decreased adherence were difficulty in reaching physicians, fear of infection and unavailability of medications.…”
Section: Discussionmentioning
confidence: 99%
“…Reasons for decreased adherence were difficulty in reaching physicians, fear of infection and unavailability of medications. 39 They also showed that for some therapies, where patients were not required to attend the clinic, the use of telemedicine was crucial to ensure continuity of treatment. 39 More research on medication adherence during COVID-19 is warranted across other chronic medical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, community pharmacists who conducted medication reviews and provided educational counseling were the most common in the 9 included literature searches [16-24]. These are followed by specialized care services for speci c diseases or illnesses being offered by community pharmacists, as underlined in 9 included studies; these services include the management of anticoagulation, minor ailments, epilepsy care, chronic pain intervention, obesity, weight services, medicine and alcohol consultation, and other chronic disease care such as diabetes and hypertension [16,20,[25][26][27][28][29][30][31] Among the included studies, 3 highlighted the expansion of community pharmacists' services and their responsibilities in preserving the continuity of care for society during public health emergencies [32][33][34]. Community pharmacists also contributed to chronic disease management during the COVID-19 pandemic, maintaining the drug supply to the public, serving as vaccinators and screeners, and performing COVID-19 diagnostic tests.…”
Section: Study Selectionmentioning
confidence: 99%
“…Community pharmacists also played a role in preserving continuity of care for people with chronic diseases during the COVID-19 pandemic. Nonadherence has been widely reported for many chronic treatments for diseases, in ammatory diseases, and osteoporosis; these treatments are interrupted and subsequently reduced in adherence and therapy discontinuation due to di culties reaching healthcare facilities and the unavailability of medications [33]. Due to being highly accessible at any time during the outbreak, more than 50% of the vulnerable population with chronic diseases relied on community pharmacists for chronic disease management care, including medication [56].…”
Section: Community Pharmacist Serve As a Focal Point During Public He...mentioning
confidence: 99%
See 1 more Smart Citation